Changing skills required by the industries: perceptions of what makes business graduates employable - Suleiman, Ebi Shahrin; Baharun, Rohaizat; Simpol, Mohd. Sallehuddin (Universiti Teknologi Malaysia, 2004)

(untitled)
This study relates to the employers assessment of graduates skills as deem required by the industries. The business need for accelerated performance levels induces a responding desire for rapid changes in the skills required by universities graduates. A changing environment with resultant organizational restructuring means graduates now find jobs are more demanding as the needs of business to be more competitive. Whereas in the past, managerial competence went hand in hand with the possession of specific skills and abilities, it now seems to involve more. Empirical evidence from the research suggests that respondents share a basic commitment to the development of common skills within the context of a business and management studies programme. Clearly the employers participating in this study placed greater emphasis on major subjects of management and business (53.5%) and less on elective subjects (18.4%). Interestingly, the Quality Assurance Unit in Ministry of Higher Education in Malaysia also made a guideline of 50-60% of major subjects in Management and Business programme for undergraduate programme. On the other hand, this study confirmed that the industry also have the same views on programme composition in Management and Business programme in Malaysia.In-term of key skills in management and business programme, verbal and written communication skill were ranked higher and less on innumeracy skill. This finding also supported findings in the programme structure, where is the communication subject must play an important role in designing management and business syllabus. In academic and intellectual skills, be independence and ability to solve business problem placed most important skills by the employers. In line with that result, the employers also expected that the graduates will be able to carry out responsibilities assigned and always on time or can keep appointments. From this finding, it is imperative that higher learning institutions gave greater emphasis in developing soft skills of the students as well as preparing them with good attitude for employment.